The Investigation of Properties and Production of CNT and BNNT Reinforced ZnO Nanocomposites - Güler, Seval Hale; Güler, Ömer (Muş Alparslan Üniversitesi, 2017)
Many reinforces have been made to improve the electrical and optical properties of ZnO. There are also nanotubes among these additives. Carbon nanotubes (CNTs) improve the electrical properties of ZnO, but the expected effect on optical properties has not been observed. In this study, CNTs produced by CVD method  and Boron Nitride nanotubes (BNNT) produced by mechanothermal method under laboratory conditions into commercial ZnO were investigated by adding together. For this purpose, CNT 50% wt. and BNNT 50%  wt. at two different rates of 0.1% and 1% was added  to ZnO. The nanotubes/ZnO  powder mixtures produced in this way are compacted and sintered. The electrical and the optical properties of the produced samples with UV-Vis spectrometer were investigated. Electrical conductivity has also been found to increase with the increase in the amount of nanotubes. However, it was observed that the reflectance properties were partially increased.

ZnO’nınelektriksel ve optik özelliklerini geliştirmek adına daha önce pek çokkatkılandırma yapılmıştır. Bu katkılar arasında nanotüplerde vardır. Karbonnano tüpler (KNT) ZnO’nun elektriksel özelliğini geliştirirken optiközelliklerinde beklenen etki görülmemiştir. Bu çalışmada ticari ZnO içerisinelaboratuvar şartlarında CVD yöntemi ile üretilen KNT ile mekanotermal yöntemile üretilen Bor Nitrür nanotüplerin (BNNT) beraber ilave edilerek etkileriaraştırılmıştır. Bu amaçla ZnO içerisine ağ. %50’si  KNT ve ağ.%50’si BNNT olacak şekilde %0.1 ve%1 gibi iki değişik oranlarda ilave edilmiştir. Bu şekilde üretilennanokompozit tozlar kompaklanıp, sinterlenmiştir. Üretilen numunelerin elektrikiletkenliği ve UV-vis spektrometre ile optik özellikleri incelenmiştir.Elektrik iletkenliklerinde, nanotüp miktarının artması ile artığı tespitedilmiş. Ancak  reflektans özelliklerindekısmen artış olduğu gözlenmiştir.
KNT ve BNNT Takviyeli ZnO Nanokompozitlerin Üretimi ve Özelliklerinin Araştırılması
msufbd
Keywords: Boron nitride nanotube; carbon nanotube; zinc oxide; Bor nitrür nanotüp; çinko oksit; karbon nanotüp